AN INDEPENDENT ASSESSMENT OF UNCERTAINTY FOR RADIOCARBON ANALYSIS WITH THE NEW GENERATION HIGH-YIELD ACCELERATOR MASS SPECTROMETERS. Issue 1 (3rd February 2021) - Aerts-Bijma, A T; Paul, D; Dee, M W; Palstra, S W L; Meijer, H A J
ABSTRACT: The radiocarbon ( 14 C) dating facility at the Centre for Isotope Research, University of Groningen went through a major upgrade in 2017 and this included installation of a MICADAS accelerator mass spectrometer (AMS). In the first 18 months, we performed 4000 sample and 3000 reference measurements. A careful evaluation of those measurement results is presented, to characterize the various sources of uncertainty and to ultimately assign, for every sample measurement, a realistic expanded uncertainty. This analysis was performed on the measurements of secondary references and sample duplicates in various phases of their processing steps. The final expanded uncertainty includes both the 14 C measurement uncertainties and uncertainties originating from pretreatment steps. Where the 14 C measurement uncertainty includes straightforward uncertainties arising from Poisson statistics, background subtraction, calibration on Oxalic Acid II and δ 13 C correction, the uncertainties originating from pretreatment steps are based on the spread of actual measurement results for secondary references and sample duplicates. We show that the 14 C measurement uncertainty requires expansion, depending on the number of processing steps involved prior to a 14 C measurement, by a maximum factor of 1.6 at our laboratory. By using these expansion (multiplication) factors, we make our reported uncertainty both more realistic and reliable.